Electrokinetic-assisted phytoremediation of heavy metal in riverbank soil - Jamari, Suhailly (2016)
Electrokinetic (EK)-assisted phytoremediation is one of the environmental remediation methods that have a big potential in enhancing the ability of plant heavy metal uptake in soils. This study was conducted to investigate the difference in heavy metal composition concentration of riverbank soil and the change of soil pH between pre and post phytoremediation and EK assisted phytoremediation treatment. The selected phytoremediation plant is Dieffenbachia ‘Tropic Rain”. The phytoremediation plant treatment was fertilized with organic and chemical fertilizer while the EK phytoremediation plant was induced with EK system (a pair of EK electrodes connected to a direct current (DC) power supply with a magnitude of 6 V/cm-1 electric field) for 4 hours/day. The soil and plant samples from pre and post treatments were analyzed using and X-ray Fluorescence Spectrometer (XRF), Scanning Electron Microscope / Energy Dispersive X-ray Spectroscopy (SEM/EDX) and Inductively Coupled Plasma Mass Spectrometer (ICP-MS). After 12 months of EK assisted phytoremediation treatment, the soil pH near the cathode increase 48.8% from pH 4.32 to pH 6.43 while in anode region the pH decrease 28% from pH 4.32 to pH 3.11. The element concentrations in cathode region for most elements of interest (Ni, Cu, Zn, As and Pb) were higher than anode and middle region with the highest is (47.3 ± 0.6) ppm Pb. The elemental concentration of Ni, Cu, Zn, As and Pb by EK assisted phytoremediation plants were slightly higher than the elements absorbed by the phytoremediation treated plants alone in the “chemical” and “organic” slots with the highest is (7.98 ± 0.68) ppb Zn. This showed that the EK assisted remediation treatment has increased the plant’s absorption during the phytoremediation process.